ENTREPRENEURSHIP ARTICLES BETWEEN THE YEARS 2015-2020: BIBLIOMETRIC AND CONTENT ANALYSES (Third Sector Social Economic Review, 2022)
Entrepreneurs, who can evaluate economic crises well changing them to advantages, play an effective role in social and economic development. In this study it is aimed to make the bibliometric analysis of the obtained 736 entrepreneurship articles published in the ""Dergipark Academic"" database between 01.01.2015 and 01.01.2021 in accordance with the criteria of ""the years the articles were published, the number of authors, the titles of the authors, the universities and the units of the authors, the journals in which the articles were published and the indexing status of these journals in the Tr Ulakbim Index"". Also, the articles were subjected to content analysis in terms of their abstracts and ""focal topics"" were revealed out. Accordingly, most of the articles were published in 2018 and mostly were written by two authors and Assist. Profs. The authors were mostly affiliated to Süleyman Demirel University and Faculty of Economics and Administrative Sciences. Obtained 736 articles were published in 323 journals, 132 of them were indexed in Tr Ulakbim Index as of 2021, and most were published in MANAS Social Studies Journal. Also, by content analysis, it is found that the articles were mostly focused on ""entrepreneurship tendency"" and ""women entrepreneurship"" topics.
Keywords: Entrepreneurship; Entrepreneurship Articles; Bibliometrics; Bibliometric Analysis; Content Analysis